Knowledge about Emergency Contraception Pills among Primary Health Care Doctors in Baghdad\Al-Karkh Sector (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Unintended pregnancy is associated with an increased risk of problems especially when woman is not in her optimal health for childbearing. The problem of unintended pregnancy and its complication can be reduced by the use of emergency contraception. Objective: To explore the knowledge of health care doctors in Baghdad/Al Karkh, Iraq regarding emergency contraception pills. Participants and Method: A structured questionnaire was distributed to a total of 390 primary health care doctors (obstetrics and gynecology specialists, general practitioners and family physicians). The questionnaire contained two main domains: demographic characteristics and knowledge about EC. Results: The majority of the sample were females 287 (73.6%), and the general practitioner (41.8%), family medicine specialists (34.6%). about one third of them were in age 40–49 years old, 72.1% of the physicians have no training about emergency contraceptive.. Conclusion: A deficit in knowledge shown by health care physicians lead to an insufficient use of emergency contraceptive pills methods.